Dampak Kebijakan Fiskal Hijau Terhadap Investasi Berkelanjutan di Indonesia dalam Perspektif Ekonomi Publik - Ahmad Wahyudi Zein; Aisyah Nur Amelia; Muhammad Rusdi Hasibuan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study uses a qualitative method to analyze the impact of green fiscal policy on sustainable investment in Indonesia from a public economics perspective. The focus of this research is on how fiscal instruments such as tax incentives, environmentally friendly subsidies, and government spending are directed to support economic growth while preserving environmental sustainability. In the context of Indonesia, which is facing challenges such as climate change and natural resource degradation, green fiscal policy has become a crucial strategy for achieving sustainable development. The study finds that well-implemented green fiscal policies can encourage investment in sustainable sectors such as renewable energy, eco-friendly agriculture, and green transportation. However, the success of these policies is highly dependent on inter-institutional synergy, data-based fiscal planning, and consistent regulatory support. The findings of this study are expected to contribute to the strengthening of Indonesia’s green fiscal policy design, which can better promote environmental protection and positively impact the long-term economy. Therefore, strong government commitment is required to position fiscal policy as a primary instrument in the transition toward a green economy.